Comprehensive sustainability assessment of a novel solar-driven PEMEC-SOFC-based combined cooling, heating, power, and storage (CCHPS) system based on life cycle method. (15th February 2023) - Zheng, Nan; Zhang, Hanfei; Duan, Liqiang; Wang, Qiushi
Abstract: Combined cooling, heating, and power systems powered by renewable energy could efficiently reduce the dependency on fossil fuels and decrease greenhouse gas emissions. This study presents a novel solar-driven proton exchange membrane electrolysis cell and solid-oxide fuel cell-based combined cooling, heating, power, and storage (CCHPS) system integrated with the parabolic trough photovoltaic-thermal (PTPVT) collector. The efficient PTPVT collector is employed to effectively generate solar electricity and thermal energy concurrently. A robust energy management strategy for optimal utilization of solar energy is proposed to smooth the solar energy fluctuations and proactively respond to the user's dynamic load demands. With the entropy weight method, a comprehensive sustainability quantitative analysis based on the life cycle method, which encompasses eleven indicators covering energy, environmental, and economic multi-attributes, is conducted to evaluate the sustainability performance of the proposed system. Meanwhile, the operating characteristics of proactively responding to the user's dynamic load demands under different operating modes and the effects of key parameters are also investigated. The results demonstrate that when the receiver side length of the PTPVT varies from 0.04 m to 0.08 m, the electric efficiency of the PTPVT declines from 24.19% to 22.93%, and the grid electricity consumption of the hybrid system increases by 16.62 MWh per year. Besides, the annual investment cost, annual net saving cost, and simple payback period are demoted by 709.52 $, 1233.01 $ and 0.09 year, respectively. The composite sustainability index of the hybrid system with a 0.04 m receiver side length of the PTPVT illustrates optimal comprehensive sustainability performance with 0.998. Highlights: A novel solar-driven PEMEC-SOFC-based combined cooling heating power and storage system is proposed. The parabolic trough photovoltaic thermal collector is used to adequately utilize solar energy. The robust energy management strategy is designed to respond to user's load demands. Comprehensive sustainability quantitative analysis based on the life cycle method is conducted. The operating characteristics of responding to dynamic demands are investigated.